Vascular smooth muscle cell growth kinetics in vivo in aged rats. - Stemerman, M B (1982)
Age is a risk factor in the development of atherosclerosis. In this study we investigated the hypothesis that proliferation of vascular smooth muscle cells (SMCs), an integral part of atherosclerotic plaque formation, changes with age. SMC growth kinetics of old rats (21-24 months) were compared to those of young adult rats (3-4 months). Rat aortas were denuded of their endothelium and the animals were killed after [3H]thymidine and Evans blue injections at 0-28 days after denudation. Incorporation of [3H]thymidine into SMC peaked in the young animals by day 2, whereas the older animals responded to endothelial removal with greater incorporation at day 2 and a more sustained rate of incorporation peaking at day 4. The [3H]thymidine incorporation curves decreased sharply from their peaks at 2 and 4 days, respectively, and paralleled each other after day 7. [3H]Thymidine uptake reflected the subsequent SMC intimal growth as measured morphometrically, with old animals showing greater numbers of intimal SMC than did the younger animals. The difference in response of SMC to injury with age suggests that aging produces a change in the vascular SMC that enhances proliferation. This change in response implies that the more pronounced atherosclerotic plaque growth seen with aging may be a result of an age-related increase in response to injury rather than merely the accumulation of time-related intimal change.